The Quality of Life of Students With Difficulties Accessing Support - Yusaku Omodaka PhD; Takeshi Sato PhD, MD (SAGE Publishing, 2023)
In recent years, the number of students enrolling in universities for higher education has increased, and these students are more diverse than ever before. Moreover, the number of students with disabilities in higher educational institutions is also increasing. Therefore, their support needs are becoming more diverse and specialized. To examine how best to provide support to students who are unable to locate it, this study conducted a survey in which details were collected from students who were involved with university student support organizations, analyze the relationship between subjective adjustment and objective adjustment, and examine the trends in subjective quality of life (QOL). In total, 156 university students (age: mean = 22.14, standard deviation = 2.86, range = 18-7) were surveyed between April 2018 and March 2020. The Japanese version of the World Health Organization Quality of Life, Brief Version, was used to analyze trends in subjective QOL. The average QOL of students who were less likely to receive support was lower than that of the general population. The results also indicated that QOL decreased as the level of disability and health status increased. Furthermore, the results of the analysis of the relationship between the overall domain QOL and the domain-specific QOL suggested that the psychological and environmental domains contributed the most to the overall QOL. Accordingly, students at universities require assistance in a number of areas. Furthermore, it is essential to adjust the content and combination of support according to the objective level of adjustment.